Circular, nanostructured and biofunctionalized hydrogel microchannels for dynamic cell adhesion studies - Kruss, Sebastian; Spatz, Joachim P. (Lab on a chip, 2012)
We report on a method to fabricate biofunctionalized polyethylene glycol hydrogel microchannels with adjustable circular cross-sections. The inner channel surfaces are decorated with Au-nanoparticle arrays of tunable density. These Au-nanoparticles are functionalized with biomolecules whereas the hydrogel material provides an inert and biocompatible background. This technology provides control over flow conditions, channel curvature and biomolecule density on the channel surface. It can be applied for biophysical studies of cell-surface interactions mimicking, for example, leukocyte interactions with the endothelial lining in small vessels.